Effect of Growing Different Leafy Vegetables as Intercrop on the Yield of Summer Colocasia in Bastar Plateau of Chhattisgarh - Shankar, Deo; Thakur, A K; Kanwar, R R; Singh, D P (JOURNAL OF ROOT CROPS, 2017)
An investigation was conducted to study the effect of leafy vegetables as intercrop on the yield of Colocasia planted during the month of December under Bastar Plateau Agroclimatic Zone of Chhattisgarh. The experiment was conducted during Rabi-Summer seasons 2014-15 & 2015-16 at Shaheed Gundadhoor College of Agriculture and Research Station (IGKV) Kumhrawand, Jagdalpur, Bastar (C.G.). The experiment was laid out in Randomized Complete Block Design (RCBD) with seven treatments. The six leafy vegetables tried as inter crops were T 1 : Colocasia + Red Amaranthus, T 2 : Colocasia + Green Amaranthus, T 3 : Colocasia + Spinach, T 4 : Colocasia + Fenugreek, T 5 : Colocasia + Coriander, T 6 : Colocasia + Mustard and T 7 : Colocasia alone was planted as contrast. Colocasia variety: Chhattisgarh Arvi-2 was used for the study. The maximum number of cormels per plant (17.84) was recorded in the treatment Colocasia + Mustard, Corm and cormel weight per plant (0.399 kg), Colocasia (33.36 t. ha - 1 ) and per ha was recorded when Colocasia was intercroped with Fenugreek in 1:1 ratio lowest duration of intercrops was for mustard (25.5 days). Maximum intercrop yield was recorded for mustard and the total system yield was for Colocasia+Fenugreek intercropping system. Fenugreek has given highest Benifit Cost Ratio (4.80) followed by spinach and red amaranthus taken in between rows of Colocasia. Intercropping Colocasia + Fenugreek, Colocasia+Spinach and Colocasia + Red Amaranthus in 1:1 ratio may be recommended to farmers for commercial cultivation during Rabi-Summer.